Desenvolvimento de um dilatômetro por micro-ondas e estudo da cinética de sinterização por método não isotérmico de materiais multiferroicos - Sandoval Ceron, Diego Mauricio (2015)
The purpose of this thesis was to develop a microwave dilatometer and to study the non-isothermal sintering kinetics of multiferroic composite ceramics. The multiferroic system used to study the sintering kinetics was a composite of two crystalline phases: piezo BaTiO3 and magnetostrictive CoxNi(1-x)Fe2O4 (where x = 0, 0.25, 0.5, 0.75 and 1 and molar ratios of 80/20, 70/30 and 50/50). A method was developed for the synthesis step, called in situ synthesis, to produce the two crystalline phases from a single solution in which the starting materials were completely dissolved. In this synthesis step, a groundbreaking method was developed for the in situ sol-gel synthesis of lead-free BaTiO3/CoxNi(1-x)Fe2O4 composites, applying synthesis control parameters such as basic pH and the amount of polyacrylic acid (PAA) added as a chelating agent. The use of basic pH and PAA as chelating agent enabled the simultaneous formation of two high purity crystalline phases with nanometric particles, spheroidal morphologies, and controlled stoichiometry. The microwave dilatometer measurement device was developed using a pyrometer sensing system, which enabled temperature measurements to be taken without the need for direct contact with the sample, and with greater accuracy, since it prevents direct interaction between the sensor and the microwave field. The effectiveness of the newly developed microwave dilatometer was tested in a study of the shrinkage behavior of the samples, which was compared with their behavior in a conventional dilatometer. The results revealed that shrinkage of the BaTiO3/CoxNi(1-x)Fe2O4 composites during microwave heating occurred at a lower sintering temperature than in conventional sintering, indicating the existence of “non-thermal” effects caused by the interaction of the sample with the microwaves. The “microwave effect” directly affected the sintering mechanisms, as evidenced by the activation energy in the initial stage of sintering. The development of the microwave heated dilatometer provided groundbreaking results in terms of reliable and reproducible dilatometric data. In addition, the in situ sol-gel synthesis of BaTiO3/CoxNi(1-x)Fe2O4 powders enabled a systematic study of the non-isothermal sintering kinetics of this material, opening up excellent prospects for the application of this technique to other materials.